Sustainability, transfer and containment properties of concrete subject to delayed ettringite formation (DEF). (October 2020) - Pichelin, A.; Carcassès, M.; Cassagnabère, F.; Multon, S.; Nahas, G.
Abstract: This work used numerous experimental techniques to evaluate the physicochemical and mechanical modifications of concrete damaged by swelling due to internal sulfate attack. The first objective was to determine property sensitive to DEF (delayed ettringite formation) and able to detect it before apparent cracking. The second objective was to quantify the evolution of the properties that impact the containment property and the sustainability of concrete after expansion and damage. It was found that gas permeability, electrical resistivity and static moduli results were the most promising techniques to detect DEF during the latency period. The loss of containment appears for damage lower than 20%.